Synergistic improvement for mechanical, thermal and optical properties of PVA-co-PE nanofiber/epoxy composites with cellulose nanocrystals. (1st March 2020) - Li, Mufang; Zhao, Xu; Li, Yingying; Wang, Wen; Zhong, Weibing; Luo, Mengying; Lu, Ying; Liu, Ke; Liu, Qiongzhen; Wang, Yuedan; Wang, Dong
Abstract: The rapid development of optoelectronic devices puts forward higher requirements for flexible transparent films with good mechanical and thermal properties. To further improve the mechanical, thermal and optical properties of the PVA-co-PE nanofiber reinforced epoxy composite film, cellulose nanocrystals (CNCs) was selected as modifier to enhance the interfacial adhesion between the reinforced nanofibers and matrix. Benefiting from excellent hydrophily, high strength, transparency and ultra-low thermal expansion coefficient (CTE) of CNCs, dramatic improvements in tensile strength, transparency and thermal stability of CNCs/PVA-co-PE/epoxy composites were observed over pure PVA-co-PE nanofiber/epoxy film. Typically, when the CNCs concentration was 3%, the transparency of CNCs/PVA-co-PE/epoxy film increased from 83.4% to 90.4%, the tensile strength increased from 11.4 MPa to 16.4 MPa, the CTE dropped from 33 to 10 ppm/K. Furthermore, as the reinforcement for matrix and the carrier for functional materials, the CNCs/PVA-co-PE nanofiber membrane was used to prepare the patterned photochromic and thermochromic films encapsulated with epoxy, indicating the potential application of CNCs/PVA-co-PE/epoxy composites in the light emitting devices. Highlights: The transparent CNCs/PVA-co-PE/epoxy film with enhanced mechanical and thermal properties was prepared. The interfacial adhesion between the PVA-co-PE nanofibers and epoxy matrix was enhanced by introduction of CNCs. The CNCs/PVA-co-PE NM is not only the reinforcement for matrix but also the carrier for functional materials. The photochromic and thermochromic films with repeatable color change properties were prepared.